Interspecific association of dominant tree species in an evergreen broadleaved forest in Phu Quoc National Park, Vietnam - Van Quy, Nguyen; Van Cuong, Le; Thanh Ha, Pham; Hong Hai, Nguyen (Journal of Forestry Science and Technology, 2023)
All species within a community either directly or indirectly interact with each other. Such interactions serve as the nucleus of both ecological and evolutionary processes. This study focused on dominant tree species’ interspecific associations and the stability of evergreen broadleaved forest stands in Phu Quoc National Park in Kien Giang province of Vietnam. The data were analyzed using the variance ratio (VR), χ2 test, association coefficient (AC), and the Godron stability method. At the end of 2022, we set up two 1-ha study plots (100 m × 100 m) in the strict protection zone within the national park to collect data. The results revealed that overall interspecific associations were significantly positive in medium and rich forests. The χ2 and AC tests indicated that associations among dominant species pairs were predominantly independent. The tree communities in the study area exhibited a relatively stable succession state. However, stability levels differed among the variety of forests. As expected, the medium forest exhibited lower stability than the rich forest. Out of the seventy-eight pairs of thirteen dominant species in each study plot, eleven significantly associated pairs were found in the medium forest, and seven significantly associated were determined in the rich forest. These significant findings should be taken into consideration when planning new afforestation or forest enrichment initiatives in areas with soil and climate conditions similar to those of the study area.